Kajian Strategis Destinasi Wisata Halal di Gorontalo dalam Perspektif Fenomenologi - Adnan, Adnan; Muhammad Tohri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This paper describes the potential opportunities for Gorontalo to develop halal tourism as a strategic destination. These opportunities are supported by several factors, including the majority Muslim population, Gorontalo's history rooted in Islamic kingdoms, and a predominance of domestic tourists. Additionally, Gorontalo City, as the capital, offers more adequate facilities compared to other cities in Gorontalo Province, such as star-rated hotels, franchise restaurants, local restaurants, and various unique Gorontalo cuisines. This research employs qualitative data analysis through field research. Data collection methods include observation, interviews, and documentation. Primary data sources are local communities as the research subjects, while secondary data sources include books, journals, online data, and other materials related to the phenomenon of halal tourism destinations. A phenomenological approach is applied to analyze the social dynamics in contemporary society, particularly in expressing spiritual (halal) lifestyle trends, as a strategic trend in halal tourism destinations in Gorontalo